Kontrowersje wokół herezji XI wieku = Controversies over Heresies of the 11th Century - Czarnecki, Piotr (Studia religiologica, 2016)
The article presents one of the most controversial issues in the history of the medieval heresies - the issue of the eleventh-century heresies - those discovered in Aquitaine (1016-1018), Orléans (1022), Arras (1025), Monteforte (1028-1040), Châlons-sur-Marne (1043-1048) and Goslar (1051). Their origins and character have been highly controversial since the middle of the 20th century. The article presents the conceptions of scholars, adherents of the two main streams of interpretation. The first of them was started by the works of the French Dominican historian Antoine Dondaine, who claimed that these heresies were dualistic in nature and were seriously influenced by the eastern heresies of this kind, mainly Bogomilism. The second one was created by the Italian Medievalist Raffaello Morghen, who believed that eleventh-century heresies were a genuine invention of the Westerners, trying to revive early, pure Christianity, based on the testimony of the New Testament. He and his followers deny their dualistic character. Besides these two streams, the article also presents the conceptions of the scholars belonging to the deconstructionist school, which has recently become more and more popular. Its adherents completely deny the existence of the eleventh-century heresies, claiming that in fact they were invented by the Church authors, trying to discredit the innocent reformers. All the conceptions mentioned above are compared with the testimonies of the sources describing the eleventh-century heresies. Their information concerning heretical beliefs and practices are strikingly similar to the analogous eastern (Bulgarian and Byzantine) sources about the Bogomils, which is a strong argument for the traditional interpretation of Dondaine and his followers.